Kemampuan pemecahan masalah matematis siswa SMP pada materi bangun ruang sisi datar: systematic literature review - Muhammad Awaludin Nasution; Rizky Rosjanuardi; Surya Kurniawan (IKIP Siliwangi, 2023)
The ability to solve mathematical problems is the goal of learning mathematics at schools both nationally and internationally. There have been many problem-solving studies on flat-sided space geometrical material at the junior high school level. Hence, this research will review these qualitative studies in the last decade. The method used is a systematic literature review (SLR) with a combination of several stages. Further, the search for articles uses the Google Scholar database with several filters and relevant keywords. A total of 35 selected articles were reviewed in this article. The study results reveal that the research trend on solving flat-sided space geometrical problems has continued from 2013 to the present. However, from year to year, the results are still similar; namely, the problem-solving abilities of junior high school students are still not satisfactory; in terms of demography, West Java dominates the research sites, and many provinces have not confirmed the results of the research are similar, in terms of material blocks and cubes occupy the most popular positions in problem-solving testing, from a theoretical point of view, Polya stages are still often used by researchers compared to other theories. 13 other variable aspects are thought to influence students' problem-solving abilities.